Perlindungan Hukum Penghayat Kepercayaan Pasca Putusan Mahkamah Konstitusi Nomor 97/PUU-XIV/2016 Perspektif Hukum Responsif - Anwar, Ahmad Syaifudin; Baskoro, Aji (UIN Sunan Kalijaga Yogyakarta, 2022)
Abstract: Indigenous People Adherents are a group that currently still exists in Indonesia. Their existence actually existed long before the existence of the Indonesian state itself. This group has spiritual values that they inherited and preserved from their ancestors in ancient times. However, their existence before the Constitutional Court Decision Number 97/PUU-XIV/2016 was often marginalized, and received discriminatory services. Finally, the Constitutional Court decided that the application for a judicial review of the Adminduk Law was contrary to the constitution. This study is a normative research library study. The data used is secondary data which consists of several legal materials including primary legal materials, secondary legal materials, and tertiary legal materials. The approach in this study is the statute approach conceptual approach, and finally historical approach. There are 2 (two) questions that the writer will examine. First, how is the protection of followers of the belief after the Constitutional Court Decision Number 97/PUU-XIV/2016. The second is how to protect Indigenous People's Adherents of the a quo Post Decision Belief in a responsive legal perspective. In this study, the authors found that the current Indonesian government has issued legal products after the quo decision. Existing regulations can at least protect them in Indonesia. Especially in the public service sector which is the main door to obtaining services and other rights. When viewed from a responsive legal perspective, it can be interpreted that the Indonesian government is in line. Even though some regulations still have not optimally regulated the protection of adherents of belief. The Indonesian government has responded well by issuing legal products after the decision of the Constitutional Court was decided.Kewords: Indigenous People Adherents; Constitutional Court; Human Rights: Responsive Law; Legal ProtectionAbstrak: Penghayat kepercayaan kepada Tuhan Yang Maha Esa merupakan kelompok yang saat ini masih eksis di Indonesia. Keberadaan mereka sebenarnya sudah ada jauh sebelum adanya negara Indonesia itu sendiri. Kelompok ini memiliki nilai-nilai spiritual yang mereka warisi dan lestarikan dari nenek moyang atau leluhur pada zaman dahulu. Namun, keberadaan mereka sebelum adanya Putusan Mahkamah Konstitusi Nomor 97/PUU-XIV/2016 kerap kali termarginalkan dan mendapatkan pelayanan diskriminatif. Akhirnya Mahkamah Konstitusi memutuskan bahwa permohonan judicial review UU Adminduk bertentangan dengan konstitusi. Kajian ini merupakan kajian library research normatif. Data yang digunakan adalah data sekunder yang terdiri dari beberapa bahan hukum meliputi bahan hukum primer, bahan hukum sekunder, dan bahan hukum tersier. Pendekatan dalam penelitian ini adalah statute approach, conseptual approach, terakhir historical approach. Terdapat 2 (dua) pertanyaan yang akan penulis teliti. Pertama, bagaimana perlindungan terhadap penghayat kepercayaan pasca Putusan Mahkamah Konstitusi Nomor 97/PUU-XIV/2016. Kedua bagaimana perlindungan terhadap Penghayat Kepercayaan Pasca Putusan a quo dalam kaca mata hukum responsif. Hasil dari kajian ini penulis menemukan bahwa pemerintah Indonesia saat ini sudah mengeluarkan produk-produk hukum pasca adanya putusan a quo. Regulasi yang ada setidaknya dapat menjadi pelindung para penghayat kepercayaan yang ada di Indonesia. Terlebih dalam sector pelayanan public yang menjadi pintu utama untuk memperoleh pelayanan dan hak-hak lainnya. Apabila ditinjau dalam kaca mata hukum responsif dapat diartikan bahwa pemerintah Indonesia telah sejalan. Meskipun memang masih terdapat beberapa peraturan yang belum optimal mengatur mengenai perlindungan terhadap penghayat kepercayaan. Pemerintah Indonesia telah merespon dengan baik dengan mengeluarkan produk-produk hukum pasca diputuskannya putusan Mahkmah Konstitusi.Kata kunci: Pengahayat Kepercayaan; Mahkamah Konstitusi; Hak Asasi Manusia; Hukum Responsif; Perlindungan Hukum